Spatial segmentation of large urban labour markets: Cultures of segregation among the urban poor? - Jacco van Golde (European Regional Science Association (ERSA), 1998)
Due to the selective process of suburbanisation of population and firms, a specific distribution of supply and demand categories has appeared within the urban space. The distribution of supply categories is more and more recognizable on the scale of neighbourhoods, both within the central city and the suburbs. The perspective of this paper is that space does not only reflect the differences in labour market chances among supply categories, but that it is also influencing these differences: the process of spatial segmentation. The question is whether the labour market chances of supply categories differs among neighbourhoods, due to personal characteristics like education, gender and etnicity and neighbourhood effects. In this paper two possible neighbourhood effects will be examined. First, the spatial distance between an individual and the location of employment will differ according to the neighbourhood where one lives. If low skilled employment is moving towards the suburbs, low skilled people in the central city will suffer due to the fact that their spatially restricted job search activities is lowering the job opportunities available for them. Second, if the population in the neighbourhood does have a low chance on the urban labour market, people might be influenced in their labour market behaviour by their neighbouring community in a negative way. The discussion of these two effects will help to provide a better insight into the nature of the problems experienced by people from the urban underclass.
Keywords: 330